Comparison of Closed Intramedullary Nailing and Percutaneous Plating in Distal Tibia Metaphyseal Fractures - Kamran Saeed, Muhammad Shahbaz Raza, Agha Momin, Naeem Mehmood Mughal, Noman Tariq, Sikander Ali Bhurgri, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the closed intramedullary nailing and percutaneous plating in distal tibial metaphyseal fractures. Study Design: Retrospective study Place and Duration of Study: Department of Orthopaedics, Sialkot Medical College, Sialkot from 1st July 2019 to 31st December 2021. Methodology: One hundred patients who were suffering from distal metaphyseal fractures of the tibia bone were enrolled. Group A patients underwent closed intramedullary nails while group B were those who were treated through percutaneous plating. Prophylactic antibiotics were given to all enrolled patients until 24 hours’ completion of the surgery. Follow-up of the wound was done from day fifth of the surgery and removal of sutures was performed by 15th day of surgery. Patients were followed up for one and a half year for their AOFAS scoring. Results: There were 58.3% males in Group A presenting a majority while in Group B females were having a majority with 47.5%. There were more left side fractures such as 53% and treated with closed intramedullary nails than through percutaneous plating. There was not a significant difference in the pain, function or alignment in both groups. There were 87% patients in group A which requested implant removal after 15.5 months while 92% of patients from Group B demanded the same. Conclusion: Intramedullary nailing is slightly superior that have reduced post-operative wound complications as compared to plate fixation.